2002
DOI: 10.1038/sj.bjp.0704672
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine interacts with the membrane of mitochondria acquiring antioxidant activity toward apoptosis – potentially implicated mechanisms

Abstract: 1 We evaluated the eects of the phenothiazine derivative thioridazine on mechanisms of mitochondria potentially implicated in apoptosis, such as those involving reactive oxygen species (ROS) and cytochrome c release, as well as the involvement of drug interaction with mitochondrial membrane in these eects. 2 Within the 0 ± 100 mM range thioridazine did not reduce the free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) nor did it chelate iron. 3 However, at 10 mM thioridazine showed important antioxidant activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 31 publications
3
49
0
3
Order By: Relevance
“…32 There is consistent evidence that quercetin presents high antilipoperoxidative activity by scavenging free radicals and chelating metals. 23 Reinforcing these concepts, it was detected that quercetin interferes with the formation of the Fe 2 (BPS) 3 complex, and additionally, the Fe-flavonoid complex maintains the free-radical scavenging activity. 8,10,33 Due to these properties of quercetin, the method used in this study was shown to be appropriate.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…32 There is consistent evidence that quercetin presents high antilipoperoxidative activity by scavenging free radicals and chelating metals. 23 Reinforcing these concepts, it was detected that quercetin interferes with the formation of the Fe 2 (BPS) 3 complex, and additionally, the Fe-flavonoid complex maintains the free-radical scavenging activity. 8,10,33 Due to these properties of quercetin, the method used in this study was shown to be appropriate.…”
Section: Discussionmentioning
confidence: 70%
“…21 This is a widely used method to evaluate antilipoperoxidative activity. 7,22,23 To 1.0 mL of medium 1, were added, respectively, 10 μL of each sample of the above prepared solutions and mitochondria to produce a final concentration of 1 mg of protein, plus 50 μmol/L of (NH 4 ) 2 Fe(SO 4 ) 2 and 2 mmol/L of sodium citrate. The solution was kept for 30 minutes at 37°C.…”
Section: + /Citrate-mediated Lipid Peroxidation Assaymentioning
confidence: 99%
“…Released cytochrome C and apoptotic protease activating factor-1 (Apaf-1) and Caspase-9 were combined, and then Cytc-Apaf-1-Caspase-9 compound was formed, which would lead to the activation of pro-Caspase-9, and subsequently, downstream Caspase-3 was activated, and apoptic cascade reaction was promoted. At the same time, part of the unreleased cytochrome C was steadily combined with cytochrome b-c1 and C oxidase, and adequate ATP was produced to provide energy for apoptosis [20][21][22][23] . The other was through necrotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests antipsychotic treatment may be related to increased antiapoptotic effects mediated by mitochondrial signals (43). Expression of antiapoptosis genes Bcl-2 and Bcl-x L is increased by haloperidol treatment (44)(45)(46), and both prevent the release of proapoptotic substances such as cytochrome c (44).…”
Section: Ultrastructure Studies Of Mitochondrial Abnormalities In Psymentioning
confidence: 99%